The Role of Academic Libraries in Improving Digital Literacy Postgraduate Students of State University of Malang: Peran Perpustakaan Perguruan Tinggi dalam Meningkatkan Literasi Digital Mahasiswa Pascasarjana Universitas Negeri Malang - Cahyono, Teguh Yudi; Masruroh, Umi (Universitas Airlangga, 2025)
Background of the study: The development of information technology requires postgraduate students to have digital literacy to support academic and research activities. Purpose: This study aims to analyze the role of Malang State University Library in improving the digital literacy of postgraduate students Method: Descriptive qualitative approach through interviews, observations, and documentation. Findings: The results show that the library plays an active role in providing access to digital resources such as electronic journals, e-books, and academic databases. Training programs on the use of reference software and literature search techniques can be organized. Digital reference and consultation services strengthen the library's technical support. Challenges include limited resources, low student participation, and lack of digitally competent librarians. Conclusion: Technology-based service innovation, AI utilization, and collaboration with external partners are needed. The findings of this study confirm the importance of innovative and collaborative library strategies in supporting digital literacy in higher education. Keywords: Digital Literacy, University Libraries, Postgraduate Students, Information Access ——————————————————————————————————————————————————————- Peran Perpustakaan Perguruan Tinggi Dalam Meningkatkan Literasi Digital Mahasiswa Pascasarjana Universitas Negeri Malang ABSTRAK Latar Belakang: Perkembangan teknologi informasi membuat mahasiswa pascasarjana memiliki literasi digital untuk mendukung aktivitas akademik dan riset. Tujuan: Penelitian ini bertujuan menganalisis peran Perpustakaan Universitas Negeri Malang dalam meningkatkan literasi digital mahasiswa pascasarjana Metode: Pendekatan kualitatif deskriptif melalui wawancara, observasi, dan dokumentasi. Temuan: Hasil menunjukkan bahwa perpustakaan berperan aktif menyediakan akses ke sumber daya digital seperti jurnal elektronik, e-book, dan basis data akademik. Program pelatihan pemanfaatan perangkat lunak referensi dan teknik pencarian literatur dapat diselenggarakan. Layanan referensi digital dan konsultasi memperkuat dukungan teknis perpustakaan. Tantangan yang dihadapi meliputi keterbatasan sumber daya, partisipasi mahasiswa yang rendah, serta kurangnya pustakawan berkompetensi digital. Kesimpulan: Inovasi layanan berbasis teknologi, pemanfaatan AI, dan kolaborasi dengan mitra eksternal sangat dibutuhkan. Temuan studi ini menegaskan pentingnya strategi perpustakaan yang inovatif dan kolaboratif dalam mendukung literasi digital di lingkungan pendidikan tinggi. Kata Kunci: Literasi Digital, Perpustakaan Perguruan Tinggi, Mahasiswa Pascasarjana, Akses Informasi